In the Labyrinths of Political Naming: Structure and Semantic Diversity of Political Party Naming - Soloviova, Tetiana; Koloiz, Zhanna (Slavistica Vilnensis, 2023)
The article reveals some problems of domestic political linguistics. Especially it’s about language sources that are used in the marketing technologies of Ukrainian political parties in the creating of some political brand-name. The essences of such terms as political brand / branding, political name / naming are found out throw the prism of interpretive linguistics and psycholinguistics. Political names are presented in formal and lexical-semantic connections. Political brand-names are qualified as mental units of the conceptual picture of the world, which accumulate various associative icons, concepts, ideas, assessments and are capable of instilling trust and creating a positive image. The focus is on complexity to find a way out of the labyrinths of the naming space for the average elector. These labyrinths contain the number of objects, renaming, consonance, duplication, etc. that don’t contribute to adequate perception, understanding, but on the contrary, lead to disorientation. Comprehension of the structure and content of political names is mostly impossible without special background knowledge, linguistic skills, etc., directly depends on the level of political culture of the electorate and civic position.